Evaluation of isthmus prevalence, location, and types in mesial roots of mandibular molars in the Iranian Population - Payman Mehrvarzfar; Nahid Mohammadzade Akhlagi; Fatemeh Khodaei; Golnaz Shojaee; Sara Shirazi (Wolters Kluwer Medknow Publications, 2014)
Background: Management of canal isthmus is considered as an important factor for successful endodontic treatment. Accordingly, this study was designed to determine the prevalence, location, and types of isthmus in mesial root canals of extracted mandibular molars in a sample of Iranian population. Materials and Methods: In this cross-sectional descriptive study, 60 extracted molars with two mesial canals were included. The samples were initially decoronated and then, roots were sectioned horizontally at 2, 4, and 6 mm levels from the apex via a low-speed handpiece with a thin metallic disk and finally prepared and stained with Indian ink. All sections were examined using a stereomicroscope at a magnification of ×30. Prevalence, location, and types of isthmus were evaluated based on the classifications by Kim and Teixeira and all data were statistically analyzed by the chi-squared test. The statistical significance level was established at 0.05. Results: Eighty-three percent of extracted mandibular molars had an isthmus at the mesial root. This prevalence increased with distance from the apex, that is, 92% at 6 mm from the apex and 70% at 2 mm from the apex. A statistically significant difference was found between the sections at 2 and 6 mm from the apex (P < 0.05), but no other significant differences between other levels (P > 0.05). Conclusion: Isthmus is very common in the mesial roots of the mandibular permanent molars in the Iranian population, with the highest prevalence in the 6 mm distance from the root apex. Therefore, detection, cleaning, and filling of these apical 6 mm isthmuses are of great benefit in modern endodontics.